2011
DOI: 10.1088/0004-637x/729/2/102
|View full text |Cite
|
Sign up to set email alerts
|

Implications of X-Ray Line Variations for 4u1822–371

Abstract: 4U 1822−371 is one of the proto-type accretion disk coronal sources with an orbital period of about 5.6 hours. The binary is viewed almost edge-on at a high inclination angle of 83 degrees, which makes it a unique candidate to study binary orbital and accretion disk dynamics in high powered X-ray sources. We observed the X-ray source in 4U 1822−371 with the Chandra High Energy Transmission Grating Spectrometer (HETGS) for almost nine binary orbits. X-ray eclipse times provide an update of the orbital ephemeris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 20 publications
13
21
0
Order By: Relevance
“…The best-fit value of the equivalent hydrogen column associated with neutral interstellar matter, N H ∼ 0.16 × 10 22 cm −2 , is similar to that obtained by Iaria et al (2001) (i.e. 0.11 +0.3 −0.5 × 10 22 cm −2 ) and to the value of ∼0.16 × 10 22 cm −2 obtained by Ji et al (2011), who fitted the HETGS spectrum of X1822-371 with a power-law component absorbed by local neutral matter. The values of equivalent hydrogen column associated with local neutral matter, N H pc , obtained by fitting the XMM and Chandra averaged spectra are compatible with each other and consistent with the value reported by Iaria et al (2001) (about 4.4 × 10 22 cm −2 ) and by Ji et al (2011) (between 5.4 and 6.3 × 10 22 cm −2 ).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The best-fit value of the equivalent hydrogen column associated with neutral interstellar matter, N H ∼ 0.16 × 10 22 cm −2 , is similar to that obtained by Iaria et al (2001) (i.e. 0.11 +0.3 −0.5 × 10 22 cm −2 ) and to the value of ∼0.16 × 10 22 cm −2 obtained by Ji et al (2011), who fitted the HETGS spectrum of X1822-371 with a power-law component absorbed by local neutral matter. The values of equivalent hydrogen column associated with local neutral matter, N H pc , obtained by fitting the XMM and Chandra averaged spectra are compatible with each other and consistent with the value reported by Iaria et al (2001) (about 4.4 × 10 22 cm −2 ) and by Ji et al (2011) (between 5.4 and 6.3 × 10 22 cm −2 ).…”
Section: Discussionsupporting
confidence: 89%
“…0.11 +0.3 −0.5 × 10 22 cm −2 ) and to the value of ∼0.16 × 10 22 cm −2 obtained by Ji et al (2011), who fitted the HETGS spectrum of X1822-371 with a power-law component absorbed by local neutral matter. The values of equivalent hydrogen column associated with local neutral matter, N H pc , obtained by fitting the XMM and Chandra averaged spectra are compatible with each other and consistent with the value reported by Iaria et al (2001) (about 4.4 × 10 22 cm −2 ) and by Ji et al (2011) (between 5.4 and 6.3 × 10 22 cm −2 ). Finally, we found that the covered X-ray emitting surface is about 60-65%.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations